2021
DOI: 10.1007/s00426-021-01508-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pain on reference memory for duration

Abstract: Previous research has consistently reported that pain related stimuli are perceived as lasting longer than non-pain related ones, suggesting that pain lengthens subjective time. However, to date, the investigation has been limited to the immediate effects of pain on time perception. The current study aims to investigate whether pain affects how a duration is recalled after a period of delay. In two experiments, participants were asked to complete four temporal generalisation tasks, where they were required fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 62 publications
(107 reference statements)
0
1
0
Order By: Relevance
“…In Experiment II, we tested the effect of the illusion on the experience of pain. Previous studies demonstrated a relation between negative experiences and the subjective time (i.e., time perception dilates when the individuals are in an unpleasant situation; Fayolle et al, 2015;Ogden et al, 2015;Piovesan et al, 2022;Rey et al, 2017). With this in mind, we expected that pain levels would be modified by their duration (i.e., if unpleasant stimuli appeared to last less time, their negative evaluation would be reduced.…”
Section: Discussionmentioning
confidence: 95%
“…In Experiment II, we tested the effect of the illusion on the experience of pain. Previous studies demonstrated a relation between negative experiences and the subjective time (i.e., time perception dilates when the individuals are in an unpleasant situation; Fayolle et al, 2015;Ogden et al, 2015;Piovesan et al, 2022;Rey et al, 2017). With this in mind, we expected that pain levels would be modified by their duration (i.e., if unpleasant stimuli appeared to last less time, their negative evaluation would be reduced.…”
Section: Discussionmentioning
confidence: 95%